Potensi Eksudat Daun Sirih Merah (Piper ornatum L.) sebagai Insektisida Herbal terhadap Mortalitas Semut Hitam - Erni Wahyuni; rizki nugrahani (Universitas Pendidikan Mandalika Mataram, 2021)
Chemical insecticide products had a negative impact on environment and health. One of the plants that can be used as an herbal insecticide is the betel plant. the red betel plant leaves are contain chemical compounds that potentialy toxic to insects, including essential oils, saponins, tannins, alkaloids and flavonoids. Black ants (Lasius fuliginosus L.) are insects that can have serious consequences if not treated, contaminate food and can transmit disease between humans and animals. The purpose of this research is to knowwing concentration is effective for black ant mortality. This research was connducted at Biology Pharmacy Laboratory of Nahdlatul Wathan University Mataram. This study consisted of 3 treatments and 2 controls (triplo for each treatment). Each repetition uses five black ants. The parameter of this study is the number of deaths per hour within three hours of the experiment. Observational data showed red betel leaf extract (Piper ornatum L) at concentrations of 25%, 50% and 75% had a significant effect on the mortality of black ants (Lasius fuliginosus L.). The higher the concentration, the more effective it is against black ant mortality. Concentration of 75% (treatment P3) has the highest effectiveness, which is 93.33%. The conclusion obtained from this study is that red betel leaf has the potential as an herbal insecticide on mortality of black ants, because red betel leaf has an effect on mortality of black ants at each concentration.